Canal-wall up cholesteatoma surgery with mastoid obliteration leads to lower rates of disease recurrence without affecting hearing outcomes - Erfurt, Chiara; Westerhout, Sanne F.; Straatman, Louise V.; Smit, Adriana L.; Stokroos, Robert J.; Thomeer, Hans G. X. M. (Frontiers in Surgery, 2024)
Objectives: The primary objective was to determine whether obliteration of the epitympanic area and mastoid cavity during canal wall up (CWU) cholesteatoma surgery reduces the rate of recurrent and residual cholesteatoma compared to not obliterating the same area. The secondary objective was to compare postoperative hearing outcomes between both techniques.Methods: A retrospective cohort study was conducted in a tertiary referral center. One-hundred-fourtythree ears were included of patients (≥ 18y) who underwent a CWU tympanomastoidectomy for cholesteatoma with or without bony obliteration between January 2015 and March 2020 in the University Medical Center Utrecht. The median follow-up was respectively 1.4 (IQR 1.1-2.2) versus 2.0 years (IQR 1.2-3.1) (p=0.013).All patients underwent CWU tympanomastoidectomy for cholesteatoma. For 73 ears bone dust, Bonalive® or a combination was used for obliteration of the mastoid and epitympanic area, the rest of the ears (n=70) were not obliterated. In accordance with the Dutch protocol, included patients are planned to undergo an MRI scan with diffusion-weighted imaging (DWI) one, three and five years after surgery to detect recurrent or residual cholesteatoma.The primary outcome measure was recurrent and residual cholesteatoma as evaluated by MRI-DWI and/or micro-otoscopy and confirmed by micro-otoscopy and/or revision surgery. The secondary outcome measure was the postoperative hearing.In this cohort, the group treated with canal wall up tympanomastoidectomy with subsequent bony obliteration (73 ears, 51.0%) had significantly lower recurrent (4.1%) and residual (6.8%) cholesteatoma rates than the group without obliteration (70 ears, 25.7% and 20.0%, respectively; p<0.001). There was no significant difference between both groups in postoperative bone conduction thresholds (mean difference 2.7 dB, p=0.221) as well as the mean air-bone gap closure 6 weeks after surgery (2.2 dB in the non-obliteration and 1.5 dB in the obliteration group, p=0.903).Conclusions: Based on our results, a canal wall up tympanomastoidectomy with bony obliteration is the treatment of choice, since the recurrent and residual disease rate is lower compared to the group without obliteration. The bony obliteration technique does not seem to affect the perceptive or conductive hearing results, as these are similar between both groups.